Self‐Healing Hyaluronic Acid‐based Hydrogel with miRNA140‐5p Loaded MON‐PEI Nanoparticles for Chondrocyte Regeneration: Schiff Base Self‐Assembly Approach - Wei Zhu; Han Wang; Bin Feng; Guangli Liu; Yixin Bian; Tianhao Zhao; Qi Wang; Xisheng Weng (Advanced Science)
Abstract Articular cartilage defects present a significant therapeutic challenge due to the inherent avascular and aneural characteristics of cartilage tissue. Gene therapy has emerged as a promising strategy for cartilage regeneration, particularly through the use of functional RNA and biomaterial‐assisted frameworks. In this study, an innovative gene‐activated self‐healing hydrogel is developed and fabricated for the controlled release of miR140‐5p, a key regulator of cartilage regeneration. The hydrogel, crosslinked via UV radiation, is composed of aminated hyaluronic acid and a modified photosensitizer (NB). To enhance the scaffold's structural integrity and gene delivery efficiency, mineralized silk fibroin and miR140‐5p‐loaded MON‐PEI nanoparticles are incorporated. These findings demonstrate that this novel hydrogel (miR140‐5p‐CaP@mSF‐HA‐NB) effectively encapsulates and releases miR140‐5p, exhibits excellent biocompatibility, and promotes enhanced cartilage regeneration in both in vitro and in vivo models. Therefore, this gene‐activated hydrogel holds significant potential for clinical applications in the treatment of articular cartilage defects.